Economic growth in the European Union - Simon György Jr (Međunarodni Problemi)
According to the empirical results expounded in the paper, the European Union’s economic growth since the 1960s has proceeded in many respects in conformity with regularities similar to those of the German economy. A combined influence was exerted by growth mechanism regularities, economic policy and international economic relations. Using models of mathematical economics, the author analyses the main relationships. The most important conclusion on the basis of empirical results is that the relatively slow economic growth of our days may be accelerated by a switch to a growth-oriented economic policy.